Періодизація та хронологія азово-дніпровської культури - Котова, Н.С. (Археологія, 2003)
У статті на основі нових радіовуглецевих дат відкореговано періодизацію та хронологію азово- дніпровської культури. Существование азово-днепровской культуры охватывает период около 1200 лет. Ее неолитический период датируется 5100—4350 гг. до н. э. и синхронизируется с сурской и киево-черкасской культурами, а также с поздними памятниками буго-днестровской культуры. Энеолитический период, синхронный Триполью А и ранней среднестоговской культуре, датируется 4350— 3900 гг. до н. э. Existence of Azov-Dnieper culture covers about 1200 years. Its Neolithic period dates from 5100 to 4350 BC and synchronized with Surskaja and Kiev-Cherkassy cultures, and also with late sites of Bug-Dniester culture. The Eneolithic period, which is synchronous to Tripol'e A and to the early faze of Sredny Stog cultures, dates from 4350 to 3900 BC.